PENGARUH PEMBERIAN EKSTRAK BEBERAPA HORMON ALAMI TERHADAP LAJU PERKECAMBAHAN TANAMAN KOPI (Coffea Sp.) - Elu, Metodius Daniel; E. Saba Agu, Yakobus Pffeferius (Savana Cendana, 2025)
This study aims to determine the effect of the administration of several natural hormones on the germination rate of coffee plants. This study used the Complete Random Design (RAL) method of a single factor pattern, which consisted of 4 treatments, namely water (M0), mung bean extract (M1), coconut water (M2), and shallot extract (M3). The results showed that: soaking using natural hormones had no real effect on the germination of coffee plants. Soaking using natural hormones produces different values, namely: Soaking using coconut water produces the highest normal sprout values and the lowest abnormal sprouts. the highest hypocotyl length, the highest epicot length. Soaking using mung bean sprout extract produced the highest germination rate value, the heaviest plant fresh weight (0.79 g) and the heaviest plant dry weight (0.39 g). Soaking using shallot extract produces the highest plant height. The overall results showed that soaking in water (control) for 12 hours alone was enough to influence and produce the best germination of coffee seeds in plant height, hypocotyl length, epicot length, highest percentage of normal germination, lowest percentage of abnormal germination.